2002
DOI: 10.1046/j.1365-8711.2002.06017.x
|View full text |Cite
|
Sign up to set email alerts
|

The peculiar variable V838 Mon

Abstract: V838 Mon underwent, after a first nova-like outburst in January and a usual decline, a second outburst after one month, and a third weak one again a month later. Moreover a very small increase of the temperature at the beginning of April gives us a hint on a physical process with a period of one month. We obtained a BVRIc time sequence and modelled the photometric behaviour of the object. This leads us to the conclusion that the interstellar foreground extinction has to be 0.6 < E(B-V) < 0.8 and that the quasi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
132
4

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(145 citation statements)
references
References 21 publications
9
132
4
Order By: Relevance
“…An optical depth of 0.65, reported above, leads to 5:8 < A V < 12 for the above two ratios. Our derived A V is considerably higher than those reported for about the same time period by Kimeswenger et al (2002), who found A V ¼ 1:8 and 2.4, respectively. An A V this large is almost certainly due to extinction from dust near the source from the present outburst or perhaps from some of the dust evident in the HST light-echo images (Bond et al 2003).…”
Section: The Late Spectrum (2002 December-2003 January)contrasting
confidence: 91%
See 1 more Smart Citation
“…An optical depth of 0.65, reported above, leads to 5:8 < A V < 12 for the above two ratios. Our derived A V is considerably higher than those reported for about the same time period by Kimeswenger et al (2002), who found A V ¼ 1:8 and 2.4, respectively. An A V this large is almost certainly due to extinction from dust near the source from the present outburst or perhaps from some of the dust evident in the HST light-echo images (Bond et al 2003).…”
Section: The Late Spectrum (2002 December-2003 January)contrasting
confidence: 91%
“…Soker & Tylenda (2003) proposed a stellar merging event (see also Kato 2003), but this would seem untenable in view of the apparent recurrent ejection episodes evidenced by the HST imagery (Bond et al 2003). The similarities between V838 Mon's behavior and that of M31 RV (Rich et al 1989), V4334 Sgr (Evans, Smalley, & Kimeswenger 2002), and V4332 Sgr (Martini et al 1999) have been noted by several groups (Wagner et al 2002b;Kimeswenger et al 2002;Munari et al 2002b;Bond et al 2003). Retter & Marom (2003) suggest that the object's observed behavior could be explained by an expanding central red giant that enveloped three relatively massive planets in close orbits.…”
Section: Introductionmentioning
confidence: 87%
“…(2007)) to have physical properties inconsistent with all of the nova models in Paper I. While thermonuclear-powered nova eruptions can explain the luminosities of these objects, their massive and very cool ejecta seem totally different from those of other novae (Mould et al (1990), Bond et al (2003), Munari et al (2002), Banerjee & Ashok (2002), Kimeswenger et al (2002), Soker & Tylenda (2003), Kipper, Klochkova, & Annuk (2004), Lynch et al (2004)). Does the nova model fail for these objects?…”
mentioning
confidence: 86%
“…Interest in the object has been rekindled because of the recent outburst of V838 Mon, which drew considerable attention because of its light echo (Munari et al 2002;Bond et al 2003). It is believed that V838 Mon, V4332 Sgr, and M31 RV (a red variable that exploded in M31 in 1988; Rich et al 1989) could be members of a new class of eruptive objects (Munari et al 2002;Bond et al 2003;Kimeswenger et al 2002). The cause of the outburst in these objects does not appear to be satisfactorily explained by conventional mechanisms.…”
mentioning
confidence: 99%